2020
DOI: 10.5115/acb.19.147
|View full text |Cite
|
Sign up to set email alerts
|

The supraorbital and supratrochlear nerves for ipsilateral corneal neurotization: anatomical study

Abstract: Neurotrophic keratitis is a rare corneal disease that is challenging to treat. Corneal neurotization (CN) is among the developing treatments that uses the supraorbital (SON) or supratrochlear (STN) nerve as a donor. Therefore, the goal of this study was to provide the detailed anatomy of these nerves and clarify their feasibility as donors for ipsilateral CN. Both sides of 10 fresh-frozen cadavers were used in this study, and the SON and STN were dissected using a microscope intra-and extraorbitally. The topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Despite their differences, both the supraorbital and supratrochlear nerves can be reliably dissected and used for neurotization. An anatomical study on 10 cadavers performed by Kikura et al showed that both nerves have sufficient length for ipsilateral transfer and could be rotated to the center of the orbit without damage induced by excessive tension, supporting their use for neurotization [ 78 ]. Similarly, Leyngold et al showed how a minimally invasive endoscopic technique could be used to perform an ipsilateral supraorbital nerve transfer while avoiding the complications of an open coronal approach [ 41 ].…”
Section: Cadaveric Studies Underlying Corneal Neurotizationmentioning
confidence: 99%
“…Despite their differences, both the supraorbital and supratrochlear nerves can be reliably dissected and used for neurotization. An anatomical study on 10 cadavers performed by Kikura et al showed that both nerves have sufficient length for ipsilateral transfer and could be rotated to the center of the orbit without damage induced by excessive tension, supporting their use for neurotization [ 78 ]. Similarly, Leyngold et al showed how a minimally invasive endoscopic technique could be used to perform an ipsilateral supraorbital nerve transfer while avoiding the complications of an open coronal approach [ 41 ].…”
Section: Cadaveric Studies Underlying Corneal Neurotizationmentioning
confidence: 99%
“…This challenge is addressed with SCN or minimally invasive corneal neurotization (MICN), which utilizes a healthy donor nerve graft to re-innervate the diseased cornea. [ 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 ] Surgical neurotization is an established treatment option for brachial plexus injury. [ 83 ] The idea of SCN was first discussed in 1972 by Samii.…”
Section: Surgical Corneal Neurotizationmentioning
confidence: 99%
“…Hypertensive intracerebral hemorrhage(HICH) generally contributes to a catastrophic, life-changing damage with an incidence of approximately 150 in 100,000 worldwide annually,wherein >81.3% of these damages includes severe hemiplegia in the contr-alateral limbs [1][2][3][4].The victims with a limb motor dysfunction signi cantly lose self-help ability, placing a burden on family or forfeiting social engagement to some extent [5][6][7][8][9][10]. Traditionally,fundamental interventions to hemiplegia after HICH revolve around subsequent physical rehabilitation or physiotherapy [11][12][13][14].Nevertheless,res-ultant outcomes usually are discouraging or dissatisfactory,rousing uninterrupted quest for patient-oriented therapies.Many studies conducted in both humans and rodents have demonstrated that an injured brain cortex can re-control the contralateral limbs through a neural network remodeling across perilesional regions and contralesional hemisphere after rewiring an afferent circuit [15][16][17][18].Recently,peripheral nerve transfer,which can ignite compensational cerebral plasticity,has been exploited to rescue partial knee extension or hand prehension in patients with acute accid myelitis or central neurological diseases [19][20][21][22].Noticeably,though current neurotization stays in early stage and yet need to be polished [23,24],its highlights have activated our aspiration for its extrapolation to a lower-limb paralysis after HICH,and further interrogation of maneuvers for a dexterous motion during neurotization.…”
Section: Introductionmentioning
confidence: 99%